Autoscopic phenomena: two cases of psychogenic origin - Cruzado, Lizardo (2025)
Autoscopic phenomena include autoscopic hallucination, heautoscopy, and out-of-body experiences. Although their study had been neglected due to their apparent rarity, today they constitute a fruitful source for the study of the neurobiological bases of self and ego sense of consciousness. Its etiology, secondary to organicity, consumption of psychoactive substances and primary psychiatric conditions, also allows us to peer into the eventual connections between classical psychopathology and recent findings of the most sophisticated neurobiology. We present the report of two cases of psychogenic etiology, and postulate the heuristic possibility that, on the basis of the increasing frequency of selfies and related concepts in current human life, autoscopic phenomena may also be augmenting.